Discriminatory Information Disclosure - Li, Hao; Shi, Xianwen (American Economic Review, 2017)
A seller designs a mechanism to sell a single object to a potential buyer whose private type is his incomplete information about his valuation. The seller can disclose additional information to the buyer about his valuation without observing its realization. In both discrete-type and continuous-type settings, we show that discriminatory disclosure—releasing different amounts of additional information to different buyer types—dominates full disclosure in terms of seller revenue. An implication is that the orthogonal decomposition technique, while an important tool in dynamic mechanism design, is generally invalid when information disclosure is part of the design. (JEL D11, D82, D83)